2021
DOI: 10.1038/s41598-021-98333-w
|View full text |Cite
|
Sign up to set email alerts
|

Polygenic risk for obsessive-compulsive disorder (OCD) predicts brain response during working memory task in OCD, unaffected relatives, and healthy controls

Abstract: Alterations in frontal and parietal neural activations during working memory task performance have been suggested as a candidate endophenotype of obsessive-compulsive disorder (OCD) in studies involving first-degree relatives. However, the direct link between genetic risk for OCD and neuro-functional alterations during working memory performance has not been investigated to date. Thus, the aim of the current functional magnetic resonance imaging (fMRI) study was to test the direct association between polygenic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Multiple studies have observed memory changes in OCD patients. Working memory deficits have been observed in OCD patients across a range of behavioural tests, including the canonical N-back task (Nakao et al, 2009 ; de Vries et al, 2014 ; Heinzel et al, 2021 ), the impaired performance of which was associated with increased activation of frontal brain regions. This included increased activity in the right dorsolateral prefrontal cortex (Nakao et al, 2009 ) and aberrant frontoparietal activation (de Vries et al, 2014 ).…”
Section: Dysfunctional Psychological Processes In Ocdmentioning
confidence: 99%
“…Multiple studies have observed memory changes in OCD patients. Working memory deficits have been observed in OCD patients across a range of behavioural tests, including the canonical N-back task (Nakao et al, 2009 ; de Vries et al, 2014 ; Heinzel et al, 2021 ), the impaired performance of which was associated with increased activation of frontal brain regions. This included increased activity in the right dorsolateral prefrontal cortex (Nakao et al, 2009 ) and aberrant frontoparietal activation (de Vries et al, 2014 ).…”
Section: Dysfunctional Psychological Processes In Ocdmentioning
confidence: 99%
“… 17 Many neuropsychological and imaging studies have showed the poor and slack performance of OCD patients on executive function tasks. 18 , 19 However, few studies have been performed on early- and late-onset OCD. Contrary to expectations, in the study of Segalas et al, tests evaluating executive functioning, visual memory, and verbal memory in late-onset OCD yielded worse results when compared with those of early-onset OCD.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, cognitive endophenotypes have been the most frequently documented (Vaghi, 2021 ) and have been observed even in pediatric OCD (Abramovitch et al, 2021 ). Recent evidence suggests that the polygenic risk score, a measure of genetic vulnerability toward OCD, is significantly correlated with alterations in brain activity during the performance of cognitive tasks not just in patients with OCD and their unaffected relatives, but in healthy controls (Heinzel et al, 2021 ). This result suggests the possibility of a “continuum” of genetic vulnerability to OCD that could cause subtle deficits in higher-order cognitive functions, most probably through alterations in brain development and functional connectivity.…”
Section: Genetics Neurodevelopment and Endophenotypes In Ocdmentioning
confidence: 99%